Determinants of Stock Market Performance in Nepal - Shrestha, Prakash Kumar; Subedi, Biggyan Raj (NRB Economic Review, 2014)
This paper empirically examines the determinants of the stock market performance in Nepal using monthly data for the period of mid-August 2000 to mid-July 2014. The impact of major changes in politics and Nepal Rastra Bank’s policy on lending against share collateral has also been assessed. Empirical results obtained from OLS estimations of behavioural equations reveal that the performance of stock market is found to respond positively to inflation and broad money growth, and negatively to interest rate. This suggests that, in Nepal, share investors seem to take equity as a hedge against inflation and consider stock as an alternative financial instrument. Further, availability of liquidity and the low interest rates stimulate the performance of the Nepalese stock market. More importantly, stock market has been found to respond significantly to changes in political environment and the policy of Nepal Rastra Bank. These findings help to design policies to stabilize or stimulate the share market in Nepal.